2018
DOI: 10.17977/um024v3i12018p008
|View full text |Cite
|
Sign up to set email alerts
|

Investigasi Struktur dan Energi Band Gap Partikel Nano Tio2 Hasil Sintesis Menggunakan Metode Sol-Gel

Abstract: TiO 2 is a semiconductor material that widely applied in various fields due to its superiority both in terms of physical and chemical properties. In this study, the TiO 2 nanoparticles was synthesized using sol-gel method. The synthesis of TiO 2 nanoparticles was started by reacting TiCl 3 with H 2 O and titrating with ammonium hydroxide and then following by calcination process at 600 0 C for 1.5 hours. The structural characteristic was investigated using XRD. The result shows that the TiO 2 has structure as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
5
0
5
Order By: Relevance
“…Choosing a moderately high calcination temperature needs to be considered to prevent agglomeration, which results in an increase in particle size and a decrease in the active surface area. Listanti et al [26] reported that agglomeration occurred during the calcination of Ti02 at 6oo°C. The Ti02 / metal-chlorophyll (Ti 02/M-Chl ) materials were characterized using a Diffuse Reflectance UV-Vis (DR / UV-Vis) spectrophotometer analyze the UV-Vis reflectance characteristics and calculate the bandgap energy of the material.…”
Section: Synthesis Of Ti02 / Metal-chlorophyll Materialsmentioning
confidence: 99%
“…Choosing a moderately high calcination temperature needs to be considered to prevent agglomeration, which results in an increase in particle size and a decrease in the active surface area. Listanti et al [26] reported that agglomeration occurred during the calcination of Ti02 at 6oo°C. The Ti02 / metal-chlorophyll (Ti 02/M-Chl ) materials were characterized using a Diffuse Reflectance UV-Vis (DR / UV-Vis) spectrophotometer analyze the UV-Vis reflectance characteristics and calculate the bandgap energy of the material.…”
Section: Synthesis Of Ti02 / Metal-chlorophyll Materialsmentioning
confidence: 99%
“…Gambar 5 memperlihatkan puncak serapan dari TiO2 murni dan Fe-TiO2 pada bilangan gelombang 3610 cm -1 -3786 cm -1 , merupakan vibrasi ulur gugus hidroksil [14]. Spektrum TiO2 diamati puncak serapan pada bilangan gelombang 602 cm -1 dan 786 cm -1 merupakan vibrasi Ti-O [15,16]. Substitusi dopan Fe 3+ pada struktur TiO 2 menyebabkan muncul puncak serapan baru dari vibrasi Fe-O [17,18] yang terjadi pada bilangan gelombang 1054 cm -1 -1065 cm -1 [19,20].…”
Section: B Spektrofotometer Ft-irunclassified
“…The maximum absorbance values for TiO2:(F+In) films at concentrations of 0, 5, 10, 15, and 20% were 6.08; 6.25; 6.37; 6.46; and 6.57. This is supported by the characteristics of TiO2 compounds in the anatase phase which absorb wavelengths with small values (close to the ultraviolet region) [23,24]. The addition of a mixture of Fluorine and Indium doping causes a shift in absorption towards visible light with a wavelength range from 320-700 nm (Figure 4b).…”
Section: Resultsmentioning
confidence: 69%